A Study of Employee Welfare Leading to Corporate Sustainability in Garments Industries of Bangladesh - Nusrat, Mansura; Solaiman, Mohammad (Asian Business Review, 2016)
Employee welfare is an area of social welfare, which covers a broad field of Corporate Sustainability and connotes a state of well-being, happiness, satisfaction, conservation and development of human resources. Evidences from contemporary literature suggest that employee welfare contributes to the sustainability of the business significantly. This paper is based on descriptive and inferential research. This study has tried to measure the extent to which the garments industries in Chittagong city of Bangladesh are providing their employees (plant level) with welfare facilities. The findings of this study suggests that most of the sample farms offer welfare benefits to their employees and such benefits have improved the productivity and sustainability of the business. The study also opens avenue for further research in this field considering employee welfare reporting as a tool for corporate sustainability in the developing counties.
Keywords: Readymade Garments; Employee welfare Facilities; Sustainability; Productivity; Satisfaction; Bangladesh